Two Putative Interleukin-1 beta Molecules Involved in the Immune Response of Seriola aureovittata - Lin WANG; Bin WANG; Yongjiang XU; Changtao GUAN (Progress in Fishery Sciences, 2023)
Interleukin-1 beta (IL-1β) is the quintessential pro-inflammatory cytokine, playing important roles in immune cell proliferation, differentiation, and apoptosis. The IL-1β genes have been characterized for many fish species. Unlike mammalian genes, several species of fish possess two IL-1β genes, which may be a consequence of genome duplication in particular fish lineages. Yellowtail kingfish (Seriola aureovittata) is a pelagic marine finfish species, which is an emerging candidate for the aquaculture industry. Therefore, details encompassing the role of IL-1β in the immune response aids a development strategy for economic and efficient aquaculture. In the present study, two novel il-1β molecules were identified from S. aureovittata (designated as SaIL-1β1 and SaIL-1β2). The full-length cDNA of SaIL-1β1 was 1 292 bp with a 828 bp open reading frame, encoding a polypeptide of 275 amino acids, while the full-length cDNA of SaIL-1β2 was 1 337 bp with a 960 bp open reading frame, encoding a polypeptide of 319 amino acids. Both SaIL-1β molecules contain an IL1 domain, 12 β-sheets, and a C-terminal conserved region, which are IL-1 family signature characters. A phylogenetic analysis revealed the fish IL-1βs clustered together. SaIL-1β1 and IL-1β in Seriola dumerili initially clustered together. However, SaIL-1β2 initially clustered with IL-1β in Trachinotus ovatu. Real-time PCR showed the transcripts of SaIL-1β1 and SaIL-1β2 were present in all the tested tissues, including the head kidney, spleen, liver, gill, heart, stomach, pituitary gland, muscle, and brain. Among them, the SaIL-1β1 transcripts were predominantly in the head kidney, spleen, and liver. The expression of SaIL-1β2 mRNA was predominantly in the gill, head kidney, and spleen. The high expression of SaIL-1β1 and SaIL-1β2 mRNA in the immune related organs implies a potential role in immune regulation. LPS is a pro-inflammatory endotoxin used as a standard immune activating agent. After LPS stimulation, the two SaIL-1βs transcripts were vigorously altered in the head kidney and spleen. SaIL-1β1 transcripts were significantly increased at 6 h, 12 h, 24 h, 48 h, and 72 h post-stimulation in the head kidney (10.03, 7.15, 4.09, 2.71, and 3.03-fold of the control group results, respectively) (P < 0.05). Meanwhile, SaIL-1β2 transcripts significantly increased from 6 h to 24 h post-stimulation after infection in the head kidney (11.49, 4.08, and 4.70-fold of the control group, respectively) (P < 0.05), had returned to normal at 48 h, and had decreased at 72 h (to 0.29-fold of the control group) (P < 0.05). In the spleen, SaIL-1β1 transcripts were sharply elevated at 6 h (to 6.59-fold of control group), gradually returned to normal at 12 h, 24 h, and 48 h (3.85, 4.09, 2.17, and 2.65-fold of control group, respectively) (P < 0.05), and had dropped to basal level by 72 h. SaIL-1β2 mRNA had a similar expression pattern to SaIL-1β1. SaIL-1β2 mRNA increased from 6 h to 48 h post-stimulation after infection (7.25, 3.20, 1.59, and 1.59-fold of the control group, respectively) (P < 0.05) and had returned to normal by 72 h. The activated immune signaling promoted the expression of SaIL-1β1and SaIL-1β2 in the immune response, especially in the early stage, indicating they might be a pro-inflammatory cytokine in S. aureovittata. Collectively, the conserved structure and tissue distribution of SaIL-1β1 and SaIL-1β2, together with their sensitivity to LPS stimulation suggests their involvement in the immune response, providing clues to our understanding of the role of IL-1β in S. aureovittata during immune response.